A novel investigation of the N2(C3Πu−B3Πg)and N2(C″5Πu−A′5Σg+)band systems using accurate functional forms. (September 2020) - da Silva, Ramon S.; Ventura, Laiz R.; Fellows, Carlos E.; Ballester, Maikel Y.
Highlights: Spectroscopic properties for five low-lying electronic states of N2 are obtained using ab initio based analitical potential energy curves. Franck-Condon factors, r-centroids, Einstein coefficients and radiative lifetimes for the second positive ( ( C 3 Π u − B 3 Π g ) ) and Herman infrared ( C ″ 5 Π u − A ′ 5 Σ g + ) bands are reported. Perturbations in the spectrum of the second positive system can be attributed to N2 (C″ 5 Πu and N 2 A ′ 5 Σ g + state. Abstract: We present a detailed investigation about the vibronic (vibration-electronic) transition parameters as Franck-Condon (FC) factors, r-centroids, Einstein coefficients, and radiative lifetimes for some bands of the second positive ( C 3 Π u − B 3 Π g ) and Herman infrared ( C ″ 5 Π u − A ′ 5 Σ g + ) band systems of N2 . For such, novel and accurate functional forms are reported. To achieve our goals, ab initio electronic energies have been obtained employing the highly accurate multireference configuration interaction (MRCI) method with Davidson modification associated with aug-cc-pVXZ (X = 5, 6) basis set. The present analytical representations were 'constructed by fitting such accurate energies utilizing a least-squares fitting procedure. By considering our Analytical Potential Energy Curves (APECs), we derived molecular properties as spectroscopic parameters, rovibrational levels, and classical turning points. Our results are compared with available experimental and theoretical data. In addition, we demonstrate that observed perturbations in the experimental spectrum of the second positive system can be also attributed to N2 (C″ 5 Πu ) and N 2 ( A ′ 5 Σ g + ) . Other important effects of these perturbations are presented.